Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru Di SMK Negeri 1 Banda Aceh - Suci Yonida Sari; TM Jamil; Irma Anggraini (Jurnal Ilmiah Mahasiswa Pendidikan Ekonomi, 2019)
This study entitled "The influence of the principal's leadership style on teacher performance in SMK Negeri 1 Banda Aceh". This research was conducted in SMK Negeri 1 Banda Aceh aims to know the influence of principal leadership style on teacher performance. . This research uses descriptive method with quantitative approach. As for the population in this study are all teachers of civil servants in SMK Negeri 1 Banda Acehyang amounting to 61 teachers and the sample is 61 teachers because the population under 100 people. Sample determination is done by Total Sampling. Technique Data collecting in this research is library research and field research by way of observation, and division of questionnaire (Questionnaire). Data analysis techniques use simple linear regression. The results of this study were (1) Principal leadership style of SMK Negeri 1 Banda Aceh 44 teachers 72.1% democracy, 7 teachers 11.5% authoritative, and 10 teachers 16.4% laissez faire. Principal leadership style of SMK Negeri 1 Banda Aceh is included in the style of democratic leadership. (2) teacher performance in SMK Negeri 1 Banda Aceh average score 86,4590% and included in medium category. (3) Based on data analysis using correlation found r value = 0,45 or 45%. Where the value of r 0 means a positive relationship between the principal's leadership style on teacher performance. The determinant correlation value shows the influence of the principal's leadership style on teacher performance by 0.20 or 20%. So it can be concluded that the principal leadership style of teacher performance in SMK Negeri 1 Banda Aceh amounted to 0.20 or 20%. Furthermore, to test the significance is done by testing t-Test and got the result of tcount of 3,876 at level of dk = 59 with error level 5% bigger than ttable value equal to 2.000 this mean Ha accepted and Ho rejected. The conclusion that can be drawn from this research is there is a significant positive influence between principal leadership style on teacher performance in SMK Negeri 1 Banda Aceh.